Assessment of Genetic Diversity of aromatic rice genotypes for BPH resistance using SSR marker - Shailendra Pratap Singh; Pushendra Kumar; Mukesh Kumar; M.K. Yadav; Mukesh Kumar; Hem Singh; Rajendra Singh (The Bioscan, 2025)
Nilaparvata lugens L., also known as the Brown Plant Hopper (BPH), is one of the most damaging insect pests that significantly reduces the output of the majority of rice varieties in Asia and India. A normal phloem feeder, that is. Thus, the current work was conducted to molecular characterize the BPH population using SSR markers in order to provide a thorough understanding of the diversity of BPH in aromatic rice germplasm. Finding the presence of brown planthopper (BPH) resistance genes in certain rice varieties is the primary objective of the current study in order to supply starting material for the breeding program of BPH resistant rice varieties. In this study, several molecular markers were used, such as RM185, RM216, RM209, RM463, and RM588 etc, and associated with BPH resistance genes Bph4, Bph12, Bph10, QBph4.2, and Bph7. The average PIC value for all the amplified SSR marker was 0.186 and the average number of polymorphic alleles was 47.00. The resolving power range between 3.708- 1.833. All 48rice germplasm were categorized into three clusters. cluster I had maximum germplasm by UPGMA. This leads to the conclusion that molecular screenings of rice crops employing SSR markers gave sufficient knowledge on biotic tolerance traits at the molecular level. This research will be used in future strategic crop enhancement breeding programs.